A Literature Study of Hybrid Fibre Reinforced Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
The drawbacks are that the concrete has  been improved by using hybrid fibre in concrete. By  hybridization benefits from two different fibres are utilized  in a single concrete mixture. The hybrids fibres studied are  basalt-polypropylene fibre, polypropylene-steel fibre, steel coconut fibre, polypropylene-e-waste fibre, polypropylene polyvinyl Alcohol and steel-glass- polypropylene fibre. The  properties that are improved using hybrid fibres are  compressive strength, tensile strength, flexural strength,  limited crack propagation, and improved durability of the  concrete structure. In maximum cases slump value decrease  with an increase in fibre percentage.
Keywords: Polypropylene Fibre; Crack Bridging; Hybrid Fibre Reinforced Concrete